2019
DOI: 10.1038/s41598-019-50101-7
|View full text |Cite
|
Sign up to set email alerts
|

Cold Preflush of Porcine Kidney Grafts Prior to Normothermic Machine Perfusion Aggravates Ischemia Reperfusion Injury

Abstract: Normothermic machine perfusion (NMP) of kidney grafts is a promising new preservation method to improve graft quality and clinical outcome. Routinely, kidneys are washed out of blood remnants and cooled using organ preservation solutions prior to NMP. Here we assessed the effect of cold preflush compared to direct NMP. After 30 min of warm ischemia, porcine kidneys were either preflushed with cold histidine-tryptophan-ketoglutarate solution (PFNMP group) prior to NMP or directly subjected to NMP (DNMP group) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…During NMP, 11.2 mL/h of a nutrient solution comprised of Nutriflex ® peri (B. Braun, Melsungen, Germany), Cernevit (Baxter, Unterschleißheim, Germany) and insulin (Insuman Rapid, Sanofi-Aventi, Frankfurt a.M., Germany) was added to all groups, as previously described by our group [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…During NMP, 11.2 mL/h of a nutrient solution comprised of Nutriflex ® peri (B. Braun, Melsungen, Germany), Cernevit (Baxter, Unterschleißheim, Germany) and insulin (Insuman Rapid, Sanofi-Aventi, Frankfurt a.M., Germany) was added to all groups, as previously described by our group [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The determination of has been performed in numerous preclinical and clinical NMP studies, which have focused on therapeutic strategies [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ], the ideal NMP experimental setup [ 42 , 43 , 44 , 45 , 46 , 47 ], or the performance of NMP compared to other preservation methods [ 48 , 49 , 50 ], among others. In these studies, either Fick’s principle (e.g., [ 35 , 42 ]) or the simplified form, the arteriovenous pO 2 difference without consideration of hemoglobin concentration (e.g., [ 37 , 39 ]), served as the basis for calculation.…”
Section: Discussionmentioning
confidence: 99%
“… 40 , 47 , 48 The precise role of a brief NMP resuscitation in clinical use has not been solidly established yet, and we await the results of the multicenter randomized clinical kidney trial in the United Kingdom. 49 Alternatively, in a different experimental NMP model, Fabry et al 50 recently demonstrated good outcomes when avoiding cold preflush before NMP, and thus going directly from nephrectomy to NMP. These results are interesting, yet controversial, as removal of blood and organ cooling is clinical practice and is thought to be fundamental in organ preservation.…”
Section: Discussionmentioning
confidence: 99%